Transitioning to Transit-Oriented Development: the Case of Perth, Western Australia - Curtis, Carey (Routledge - Taylor and Francis Group, 2012)
Perth has seen one of the most deliberate attempts worldwide to move from car-dependent development patterns to transit-oriented development (TOD). State planning policy has required TOD for the past 20 years, the public transport network has been progressively improved and the institutional arrangements are strong. Three different town planning models have been applied to implement TOD. A series of research investigations examine the land-use response to TOD policy including land-use mapping, policy content analysis and interviews with local government. The findings suggest that transition to TOD requires policy clarity and consistent application, considered integration of land-use planning and transport planning actions at the project level, and incentives for local government and development industry.